إلزامية الوعد في المصارف الإسلامية من منظور الفقه الإباضي : سلطنة عمان أنموذجا - عبد الله، منذر سالم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This study aims to identify the reality of Islamic banks in the Sultanate of Oman , the issue of promise and the conditions of some Islamic contracts offered by the bank and differences of opinion between the Islamic Jurisprudence scholars from Ibadi School as it is the official doctrine in the Sultanate of Oman . Besides that , some stated views from the Sunni Scholars from various collected sayings regarding the issues have been included within this research as well in order to illustrate the differences between the Ibadi School and the doctrines of the Sunnis by mentioning of contracts related to the matter , the study tried to answer the following questions: what is the reality of banks or Islamic banks in the Sultanate of Oman do they have an active role in the service of the Omani society in particular ? Is Ibadi School differs from Sunni sects in the issue of promise? Since the banks are still in the process of contract structuring , what tool is currently being used in those banks or Islamic windows ? Thus ,in order to answer the questions which are mentioned above, the researcher used several methods to gather statements from both parties and the statements of legitimate bodies with those banks or Islamic windows , and their fatwa on the issue of promise in the products offered at accredited banks in the Sultanate of Oman lectures with specialists in this area and explaination . The researcher found some valuable results . The study recommended the importance of educating the Omani society in the field of Islamic transactions , the lack of expertise in the Sultanate , the work sessions and educational training of Islamic banks .On top of that it also recommended the need to address those negative elements in the contracts offered by Islamic banks in the Sultanate of Oman in particular.